TATO DIANTARA GAYA HIDUP & INDUSTRI - Setiawan, I Nyoman Anom Fajaraditya (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Tattoos in present-day phenomena have changed in the wider space. This phenomenon is also divided into two different directions. The opening of space and the depletion of paradigm boundaries about tattoos, triggered also from external factors. These factors from the development of tourism and internet that has a wide influence on the development of tattoos in Indonesia. The division of tattoo into two-way needs that is as part of the lifestyle and part of the industry. The appearance of these two things is very clearly seen in the tourist visit areas, especially in Bali. The expression of the soul as well as the historical background symbol becomes a representation of the tattoo collector. But from an industry perspective, it provides profitable opportunities with the latest technology intermediaries. These two things also play a role in the development of tattoos in general, especially from the creativity in the creation of works and media.